USM MEDICAL LECTURER THE FIRST MALAYSIAN TO WIN REIMAGINE EDUCATION TEACHING DELIVERY AWARD - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUBANG KERIAN, 13 December 2016 A medical lecturer from Universiti Sains Malaysia (USM) has created history when he became the first Malaysian to win the world’s most prestigious award in education, the Reimagine Education Teaching Delivery Award, which was announced on 6 December 2016 in Philadelphia, United States.